1982
DOI: 10.1103/physrevlett.48.1653
|View full text |Cite
|
Sign up to set email alerts
|

Baryon Masses in a Relativistic Quark-Diquark Model

Abstract: Masses of ground-state spin-| baryons are calculated in a relativistic quark-diquark model with a potential motivated by QCD. The parameters of the model are determined by fitting vector-meson masses, and so the calculation for baryons contains no free parameters. Results are in rather good agreement with experiment. Moreover, starting from dynamical quark masses close to the so-called current masses, effective quark masses are obtained in the right range to be identified with constituent masses. PACS numbers:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…30. No enhancements show up in the spectrum, the shape of which is qualitatively similar to the background in the right sign combinations, as can be seen in Figure 5.31.…”
Section: Candidate Selectionsupporting
confidence: 55%
See 1 more Smart Citation
“…30. No enhancements show up in the spectrum, the shape of which is qualitatively similar to the background in the right sign combinations, as can be seen in Figure 5.31.…”
Section: Candidate Selectionsupporting
confidence: 55%
“…Because the strong coupling constant α s is large for interactions involving small momentum transfer, masses and decay widths of the heavy-quark states cannot be calculated within the framework of perturbative QCD. As a result, many different approaches have been developed, for example, based on heavy-quark effective theory (HQET) [29], nonrelativistic and relativistic potential models [30], or lattice QCD [31].…”
Section: Theoretical Predictions and Experimental Statusmentioning
confidence: 99%
“…There is good phenomenological evidence that in a rotationally excited baryon a quark-diquark (q − D) structure is favored over a three-quark (qqq) structure [8], [9], [10] . Eguchi [11] had shown that it is energetically favorable for the three quarks in a baryon to form a linear structure with a quark on one end and bilocal structure qq at the other end.…”
Section: Introductionmentioning
confidence: 99%
“…Because the strong coupling constant α s is large for interactions involving small momentum transfer, masses and decay widths of the heavy-quark states cannot be calculated within the framework of perturbative QCD. As a result, many different approaches have been developed, for example, based on heavy quark effective theory (HQET) [3], non-relativistic and relativistic potential models [4], or lattice QCD [5].…”
mentioning
confidence: 99%